Proposed upgrading Wifi services and facilities at level three (3) and four (4) of KAED building - Johari, Mohd Helmi; Ayob, Mohd Fairullazi (2017)
This presentation slides are prepared to deliberate in Kulliyyah meeting with the objective to seek approval from the relevant university to upgrade Wi-Fi facilities on improving Wi-Fi network services performance of Levels three (3) and four (4) of KAED building at the Kulliyyah of Architecture and Environmental Design (KAED), International Islamic University Malaysia